2018
DOI: 10.1038/s41598-018-27949-2
|View full text |Cite
|
Sign up to set email alerts
|

Positron Annihilation Studies on Chemically Synthesized FeCo Alloy

Abstract: Equiatomic flower-like FeCo magnetic nanoparticles are synthesized through a modified one-pot polyol technique. The as-prepared samples are annealed at 700 and 800 °C under reducing atmosphere. The saturation magnetization and coercivity of the flower-like FeCo are found to be 198 (1) emu/g and 243 (10) Oe respectively. The magnetic properties of FeCo approach the bulk behavior with annealing. Positron lifetime studies on the chemically synthesized equiatomic FeCo magnetic nanoparticles with flower-like morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Hamdeh et al have shown that the value of δ is more sensitive to the 4s electrons than 3d↓ states for the FeCo alloy. It is noted that our recent studies using positron annihilation spectroscopy indicated higher fraction of cluster vacancy‐type defects in the equiatomic FeCo alloy . Therefore, the large δ value could be understood as due to the 4s electron polarization influenced by the vacancies in the FeCo alloy compared with the bulk.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Hamdeh et al have shown that the value of δ is more sensitive to the 4s electrons than 3d↓ states for the FeCo alloy. It is noted that our recent studies using positron annihilation spectroscopy indicated higher fraction of cluster vacancy‐type defects in the equiatomic FeCo alloy . Therefore, the large δ value could be understood as due to the 4s electron polarization influenced by the vacancies in the FeCo alloy compared with the bulk.…”
Section: Introductionmentioning
confidence: 89%
“…The H c of 576(5) Oe for the size‐reduced FeCo is larger than the theoretical maximum of 210 Oe and usually low coercivity of 10–50 Oe is expected for bulk FeCo . Coercivity close to 500 Oe could arise in the chemically reduced FeCo alloy of flower‐like morphology due to the shape anisotropy when there is wide inter‐petal gap . The size‐reduced FeCo particles are mostly isotropic and close to spherical morphology without any chain formation and therefore shape anisotropy contribution can be ignored.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Fe particles of varying sizes were synthesized using EG, PG, Gly, and DiMG as the reducing media availing the instant chemical reduction process exclusively developed by the authors. [90,[96][97][98][99][100] Magnetite nanoparticles were obtained in terminal polyols, such as 1,3-propanediol (t-PG) and 1,4-butanediol (t-BG), under similar experimental conditions. In a typical reaction, the polyols were heated up to 170 °C followed by the stochiometric addition of ferrous chloride tetrahydrate salt and NaOH pellets within a time interval of 5 s. The black precipitate obtained after the reaction, that lasted not more than 5 min, was cooled down using methanol and the particles were magnetically separated.…”
Section: Methodsmentioning
confidence: 99%
“…In water, due to the excess of oxygen atoms, the majority of o-Ps spins are inverted and thus the effective yield of annihilation quanta into three gammas approaches ≈ 1% 28 . The formation of o-Ps and the 3γ/2γ yield in materials can be significantly affected by open volume defects such as in the Fe 3 O 4 crystal structure of SPION cores 23,29 . The lack of collinearity of the annihilation photons due to residual momentum of the e + or Ps at the time of decay can also impact the spatial resolution in PET imaging.…”
Section: Phantom Numbermentioning
confidence: 99%